Small secretory proteins of immune cells can modulate gynecological cancers. (November 2022) - Kumar, Niranjan; Vyas, Akanksha; Agnihotri, Saurabh Kumar; Chattopadhyay, Naibedya; Sachdev, Monika
Abstract: Small secretory proteins of immune cells are mostly Cytokines, which include chemokines, interleukins, interferons, lymphokines and tumor necrosis factors but not hormones or growth factors. These secretory proteins are the molecular messengers and primarily involved in autocrine, paracrine and endocrine signaling as immunomodulating agents. Hence, these proteins actually regulate the cells of immune system to communicate with one another to produce a synchronized, robust, still self-regulated response to a specific antigen. Chemokines are smaller secreted proteins that control overall immune cell movement and location; these chemokines are divided into 4 subgroups, namely, CXC, CC, CX3C and C according to the position of 4 conserved cysteine residues. Complete characterization of cytokines and chemokines can exploit their vast signaling networks to develop cancer treatments. These secretory proteins like IL-6, IL-10, IL-12, TNFα, CCL2, CXCL4 & CXCL8 are predominantly expressed in most of the gynecological cancers, which directly stimulate immune effector cells and stromal cells at the tumor site and augment tumor cell recognition by cytotoxic T-cells. Hence; these secretory proteins are the major regulators, which can actually modulate all kinds of gynecological cancers. Furthermore, advancements in adoptive T-cell treatment have relied on the use of multiple cytokines/chemokines to establish a highly regulated environment for anti-tumor T cell growth. A number of in vitro studies as well as animal models and clinical subjects have also shown that cytokines/chemokines have broad antitumor activity, which has been translated into a number of cancer therapy approaches. This review will focus on the foremost cytokines & chemokines involved in the majority of the gynecological malignancies and discuss their basic biology as well as clinical applications.